2012
DOI: 10.1016/j.jvs.2011.12.056
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent prophylactic placement of inferior vena cava filter in gastric bypass and adjustable banding operations in the Bariatric Outcomes Longitudinal Database

Abstract: Introduction: Postoperative pulmonary embolism (PE) is a leading cause of morbidity and mortality after bariatric surgery. However, the concurrent prophylactic placement of an inferior vena cava filter (CPIVCF) in patients undergoing bariatric operations remains controversial. This study used the Bariatric Outcomes Longitudinal Database (BOLD) to establish associated characters and determine outcomes of CPIVCF for patients undergoing Roux-en-Y gastric bypass (GB) and adjustable gastric banding (AB) surgeries. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 40 publications
0
12
0
2
Order By: Relevance
“…Of the 701 selected abstracts, we included 6 studies (n=102767) for the quantitative synthesis ( Figure 1) [7][8][9][10][11][12] . Studies were published between 2006 and 2013, and all patients underwent bariatric surgery ( Table 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 701 selected abstracts, we included 6 studies (n=102767) for the quantitative synthesis ( Figure 1) [7][8][9][10][11][12] . Studies were published between 2006 and 2013, and all patients underwent bariatric surgery ( Table 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…It is possible, even though only one study [10] adjusted for important differences between the groups, that some of these patients may be sicker at baseline compared to those obese patients where the surgeon did not consider the placement of an IVC filter before surgery. For example, some of the patients belonging to these groups could be older, more obese, have a greater limitation in functional status and longer duration of surgery.…”
Section: Mortality Related To Prophylactic Ivc Filter Placement Beformentioning
confidence: 99%
“…We identified 2 systematic reviews of RCTs and observational studies 137,138 that addressed this research question in bariatric surgery and trauma patients. We identified 14 studies [139][140][141][142][143][144][145][146][147][148][149][150][151][152] in these reviews that fulfilled our inclusion criteria and measured outcomes relevant to this context. Our search for RCTs and observational studies identified 1 additional study that fulfilled the inclusion criteria.…”
Section: Recommendationmentioning
confidence: 99%
“…Maybe we could have used a combined drug and mechanical thromboprophylaxis strategy as it was done recently for a hip arthroplasty in a severe FXIdeficient patient using Hemoleven [27]. Regarding the placement of inferior vena cava filter for primary prophylaxis, several nonrandomized trials did not show a significant difference in rates of VTE [28][29][30][31], expect one. In the latest issue of Chest from the American College of Chest Physicians [17], it is stated that 'for abdominal-pelvic patients we suggest that an inferior cava filter should not be used for primary prevention (grade 2C)'.…”
Section: Discussionmentioning
confidence: 99%